Konsep Kepemimpinan dalam Islam - Ahmadireja (Tarbiyah Departement collaboration with AMCA, 2014)
Leadership in Islam occupies a very strategic position. Because leadership is an instrument to achieve the lofty ideals of a nation. Namely the creation of a nation that